Cover Picture: Efficient Trapping of Trace Acetylene from Ethylene in an Ultramicroporous Metal–Organic Framework: Synergistic Effect of High‐Density Open Metal and Electronegative Sites (Angew. Chem. Int. Ed. 43/2020). Issue 43 (7th September 2020) - Zhang, Zhaoqiang; Peh, Shing Bo; Wang, Yuxiang; Kang, Chengjun; Fan, Weidong; Zhao, Dan
Abstract : The co‐existence of high‐density open metal sites and electronegative sites in confined ultramicropores is a big challenge. In their Communication on page 18927, D. Zhao et al. demonstrate that such sites co‐existing in ultramicroporous channels of a metal–organic framework can synergistically interact with acetylene, leading to excellent capture performance in the removal of trace acetylene from ethylene.